2004
DOI: 10.1007/s00427-004-0440-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutated otopetrin 1 affects the genesis of otoliths and the localization of Starmaker in zebrafish

Abstract: Otoliths in bony fishes and otoconia in mammals are composite crystals consisting of calcium carbonate and proteins. These biominerals are part of the gravity and linear acceleration detection system of the inner ear. Mutations in otopetrin 1 have been shown to result in lack of otoconia in tilted and mergulhador mutant mice. The molecular function of Otopetrin 1, a novel protein that contains ten predicted transmembrane domains, however, has remained elusive. Here we show that a mutation in the orthologous ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 23 publications
(30 reference statements)
3
81
0
Order By: Relevance
“…However, demonstrated that the vestibular ganglia in Nox3 het and Otop1 tlt adult mice are spontaneously active with mature discharge rates and patterns, a phenomenon that presumably requires functional hair cell to afferent transmission. The Otop1 gene encodes a novel 10 transmembrane domain protein (Hurle et al, 2003) that influences Ca 2+ fluxes (Hughes et al, 2007) and may be involved in protein secretion (Sollner et al, 2004). Otop1 is also expressed in the sensory epithelium of the inner ear, both hair and supporting cells (Hurle et al, 2003;Sollner et al, 2004).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, demonstrated that the vestibular ganglia in Nox3 het and Otop1 tlt adult mice are spontaneously active with mature discharge rates and patterns, a phenomenon that presumably requires functional hair cell to afferent transmission. The Otop1 gene encodes a novel 10 transmembrane domain protein (Hurle et al, 2003) that influences Ca 2+ fluxes (Hughes et al, 2007) and may be involved in protein secretion (Sollner et al, 2004). Otop1 is also expressed in the sensory epithelium of the inner ear, both hair and supporting cells (Hurle et al, 2003;Sollner et al, 2004).…”
mentioning
confidence: 99%
“…electrophysiological and behavioral studies show that absent or drastically altered crystal mass invariably leads to balance deficits (Trune and Lim, 1983;Anniko et al, 1988;Ornitz et al, 1998;Kozel et al, 1998;Jones et al, , 2004Simmler et al, 2000;Sollner et al, 2003Sollner et al, , 2004Paffenholz et al, 2004). However, most of the mutants used in these reports may have potentially compromised hair cells, stereocilia or vestibular ganglia due to expression of the mutant genes in these structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The zebrafish otop1 orthologue is a highly conserved gene that is essential for otolith initiation as seen in both morphant otop1 fish and in the backstroke mutant (Hughes et al, 2004;Sollner et al, 2004). Despite lack of otoliths in early development, otop1 morphant fish partially recover otolith formation after 2 days, in a timeframe consistent with dilution of the morpholino and reexpression of otop1, indicating that Otop1 has an essential and conserved role in the timing of formation and the size and shape of the developing otolith.…”
Section: Locally Increase Calcium and Carbonate Concentrations To Inimentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that the shape, size and organization of CaCO 3 crystallites in otoconia and otoliths are strictly controlled by an organic matrix (Kang et al 2008;Murayama et al, 2005;Sollner et al 2003;Zhao et al 2007). The organic components of otoconia primarily consist of glycoproteins and proteoglycans Ito et al 1994;Pisam et al 2002;Pote and Ross 1991;Verpy et al 1999;Wang et al 1998;Xu et al 2010;Zhao et al, 2007).…”
mentioning
confidence: 99%